Solution of Shortest Paths in Non-Euclidean Farey Graph with Floyd-Warshall Algorithm - Gökcan, İbrahim (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2025)
Algorithm applications on graphs are intensively researched. Graph theory systematizes complex and difficult problems and algorithms provide fast and clear solutions, which increases interest in the discipline. The Floyd-Warshall algorithm determines the shortest paths between all the vertices in a graph. In this paper, we consider the Floyd-Warshall algorithm on the Farey graph defined in a non-Euclidean hyperbolic space. A Farey graph with 15 edges and 9 vertices is constructed and the shortest paths from all vertices to other vertices are detected. By defining the weight between consecutive vertices, the shortest paths between the vertices are measured in terms of the number of steps.